Perilaku Kedermawanan Muslim di Indonesia Studi Mengenai Intensi Dan Perilaku Bersedekah - Mohamad Ivan Setianagara (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2019)
This paper is to analyzes the factors that influencing the intention and behavior of charity of Muslim society in Indonesia. What elements are the most powerful contributors in charitable intentions and does the current Muslim community in Indonesia have an addiction to charity?Theory of Planned Behavior is used to examine intention and behavior in charity. This research uses descriptive research approach to explain the profile of the respondents, their behavioral tendency incharity. This research is also trying to find out what factors affect the individual in charity so thatthis behavior becomes an addicted thing.The statistical method used in analyzing the data is the Structural Equation Modeling (SEM) method with the assisted of LISREL (Linear Structural Relation) program version 9.30.The results of the study found that the most influential factor on the intention of charity of Muslim society in Indonesia is Perceived Behavioral Control.Also illustrated that the Muslim community in Indonesia has not reached the level of "addiction" in charity. The dominant frequency of charity is 73% as much as 1 - 5 times in a month, while thehypothesis of addiction is the frequency of giving alms more than 5 times within a month.